The power of reflective journal writing for university students from the EFL perspective - Anselmus Sudirman; Adria Vitalya Gemilang; Thadius Marhendra Adi Kristanto (Universitas Syiah Kuala, 2021)
English as a foreign language (EFL) university students use reflective journals as learning logs to express or capture their ideas within a scientific conceptual framework. The objectives of this research are to (1) describe the power of reflective journal writing in communicating ideas, and (2) identify the aspects of reflective journal writing that aid learning in an EFL context. The reflective journals were written by 21 EFL university students. This research takes a qualitative approach, with the primary data coming from several reflective journals (N=124) while the secondary data coming from EFL students’ interviews (N=15). The research results showed that reflective journals were useful for students to make critical reflections and self-discovery responses to writing topics. The students learned to focus on writing components such as order, unity, coherence, cohesiveness, content, and organization of ideas through reflective journal writing. The students’ perspectives on aspects of reflective journal writing were primarily concerned with macro-and micro-level linguistic issues, as evidenced from the interview results. Writing a reflective journal necessitated their ability to reformulate thoughts, provide details, and solve problems. Furthermore, critical thinking, metacognitive skills, and self-reflections became increasingly important in helping the students to develop their ability to write reflective journals.